A Companion to Plato. - Benson, Hugh H., 1956- (Blackwell companions to philosophy., 2007)
Plato and Platonism remain fundamental to the practice of philosophy. This work includes contributions from Platonic scholars from around the world and reflects the various ways in which they are dealing with Plato's legacy. It covers topics in Platonic philosophy, ranging from perception and knowledge to politics and cosmology.